If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(1+5)+3(1-p)=-48
We move all terms to the left:
-8(1+5)+3(1-p)-(-48)=0
We add all the numbers together, and all the variables
3(-1p+1)-86-(-48)=0
We add all the numbers together, and all the variables
3(-1p+1)-38=0
We multiply parentheses
-3p+3-38=0
We add all the numbers together, and all the variables
-3p-35=0
We move all terms containing p to the left, all other terms to the right
-3p=35
p=35/-3
p=-11+2/3
| f/4-1=5 | | 0=-2t^2+20t+8 | | 11-5x=10-x | | x+3(6)=12 | | 60-b=31 | | 25+4f=81 | | 42/s=6 | | -11-8x=−-3x+19 | | 2(15-5x)=-3(21-2x) | | 123-3h=45 | | j/7-10=14 | | 3x+x-2=-78 | | S^2+s^2=169 | | 9-t=2 | | 335=-42+13v | | 2w+-2=-14 | | 35+15+0.25x=40+0.25x | | -13v=1195 | | 3x+30=12x+12 | | 4(35-2x)=2x+14 | | 6=1/3(x) | | -0.5=p/3-1.9 | | 3t+-1=-4 | | -2k+5=3 | | 16x–16=4 | | 0.59x+36=1.19x | | 2+-2s=10 | | 5x-28=-3(x-12) | | y=1/3(-18) | | x+16+x-2=28 | | -12x^2+20x-3=0 | | 0.59x+36=1.19 |